Relationship between Tumor DNA Methylation Status and Patient Characteristics in African-American and European-American Women with Breast Cancer - Wang, Songping (Public Library of Science, 2012)
Aberrant DNA methylation is critical for development and progression of breast cancer. We investigated the association of CpG island methylation in candidate genes and clinicopathological features in 65 African-American (AA) and European-American (EA) breast cancer patients. Quantitative methylation analysis was carried out on bisulfite modified genomic DNA and sequencing (pyrosequencing) for promoter CpG islands of p16, ESR1, RASSF1A, RARβ2, CDH13, HIN1, SFRP1 genes and the LINE1 repetitive element using matched paired non-cancerous and breast tumor specimen (32 AA and 33 EA women). Five of the genes, all known tumor suppressor genes (RASSF1A, RARβ2, CDH13, HIN1 and SFRP1), were found to be frequently hypermethylated in breast tumor tissues but not in the adjacent non-cancerous tissues. Significant differences in the CDH13 methylation status were observed by comparing DNA methylation between AA and EA patients, with more obvious CDH13 methylation differences between the two patient groups in the ER- disease and among young patients (age<50). In addition, we observed associations between CDH13, SFRP1, and RASSF1A methylation and breast cancer subtypes and between SFRP1 methylation and patient's age. Furthermore, tumors that received neoadjuvant therapy tended to have reduced RASSF1A methylation when compared with chemotherapy naïve tumors. Finally, Kaplan Meier survival analysis showed a significant association between methylation at 3 loci (RASSF1A, RARβ2 and CDH13) and reduced overall disease survival. In conclusion, the DNA methylation status of breast tumors was found to be significantly associated with clinicopathological features and race/ethnicity of the patients.